Solution-processed MoS2 nanotubes/reduced graphene oxide nanocomposite as an active electrocatalyst toward the hydrogen evolution reaction. Issue 75 (26th July 2016) - Song, Long; Zhao, Mengjia; Li, Xiaoxue; Zhang, Zhipan; Qu, Liangti
Abstract : A hierarchical 3D nanostructure of MoS2 nanotubes supported on a reduced graphene oxide network is prepared through a surfactant-assisted lyophilization process and it exhibits good electrocatalytic activity in the hydrogen evolution reaction. Abstract : Advanced materials for electrocatalytic water splitting are essential to the area of renewable energy. In this work, we report a hierarchical 3D nanostructure of MoS2 nanotubes supported on a reduced graphene oxide network (MNTs@rGO) through a surfactant-assisted lyophilization process. The resulting MNTs@rGO exhibited good electrocatalytic activity in the hydrogen evolution reaction (HER) relative to other representative MoS2 -based electrocatalysts, with an onset overpotential of 180 mV, a small Tafel slope of 69 mV dec −1 as well as a large cathodic current density (38.91 mA cm −2 at an overpotential of 300 mV). Linear sweep voltammetry (LSV) tests and electrochemical impedance spectroscopic (EIS) measurements reveal that the MNT building blocks with high exposure of surface atoms function as the active catalytic sites in the HER and the rGO support serves as the conductive footstone connecting all catalytic sites with fast electron transport. The EIS characterization also demonstrates that the electron transfer at the catalyst/electrolyte interface is the rate-limiting step in the catalyzed HER and assembling MoS2 nanosheets into nanotubes can significantly facilitate the HER. The current results are deemed to provide new insights into next-generation HER catalysts with high activity and low cost.